Phenotype and Metabolic Disorders in Polycystic Ovary Syndrome. (29th February 2012) - Głuszak, Olgierd; Stopińska-Głuszak, Urszula; Glinicki, Piotr; Kapuścińska, Renata; Snochowska, Hanna; Zgliczyński, Wojciech; Dębski, Romuald
Abstract : The polycystic ovary syndrome (PCOS) is one of the most frequent endocrinopathies in women. Its incidence is assessed at 6–8% of the female population in the reproductive age. It is characterised by oligomenorrhea (Oligo), hyperandrogenism (HA), and the presence of polycystic ovaries (PCOs). Carbohydrate and lipid metabolism is being disturbed in many women with PCOS. The pathogenesis of PCOS is still unexplained. Following the main criteria of diagnosis (Rotterdam Consensus 2003), Dewailly, Welt and Pehlivanov divided the patients with PCOS into 4 phenotype groups: A, B, C, and D. In our studies of 93 patients with PCOS, we found (1) the most frequent appearance (60, 2%) of the phenotype A [Oligo + HA + PCO]; (2) an increased androstenedione concentration in a group with HA (A, B, C); (3) an increased HOMA-β and insulin concentration after 30 min an oral 75 g glucose tolerance test (OGTT) in a group of obese women with BMI > 30 kg/m 2 ; (4) high levels of total testosterone, total cholesterol, and LDL cholesterol concentrations in a group A with classic phenotype of PCOS: Oligo + HA + PCO—increasing the risk of development of cardiovascular diseases, type 2 diabetes, or metabolic syndrome. The average androstenedione concentrations could be a good diagnostic and prognostic parameter.